Determinants of Earnings Quality: A Discretionary Accruals Approach in Basic Industry and Chemical Companies Listed in the LQ 45 Group for the 2019-2023 Period - Heriansyah, Kurnia; Permata, Irma Sari; Mulyadi, Mulyadi (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the impact of profitability, liquidity, financial structure, and independent commissioners on earnings quality, proxied by discretionary accruals, in basic industry and chemical companies listed in the LQ45 index for 2019–2023. The research employs a quantitative approach, using secondary data from financial reports published on the Indonesia Stock Exchange. The findings reveal that profitability and financial structure have no significant effect on earnings quality, highlighting that high profitability or solid financial structure does not necessarily ensure high-quality earnings. Liquidity exhibits a significant negative impact, suggesting that companies with stable liquidity are more efficient in meeting obligations, enhancing earnings quality. Independent commissioners also show no influence, as their presence often fulfills regulatory requirements without significantly improving monitoring effectiveness. The study emphasizes the integration of agency and signaling theories in understanding earnings quality and encourages future research to explore additional variables beyond the LQ45 group